Molecular mechanisms involved in Bacillus subtilis biofilm formation - Mielich-Süss, Benjamin (2014)
Biofilms are the predominant lifestyle of bacteria in natural environments, and they severely impact our societies in many different fashions. Therefore, biofilm formation is a topic of growing interest in microbiology, and different bacterial models are currently studied to better understand the molecular strategies that bacteria undergo to build biofilms. Among those, biofilms of the soil-dwelling bacterium Bacillus subtilis are commonly used for this purpose. Bacillus subtilis biofilms show remarkable architectural features that are a consequence of sophisticated programs of cellular specialization and cell-cell communication within the community. Many laboratories are trying to unravel the biological role of the morphological features of biofilms, as well as exploring the molecular basis underlying cellular differentiation. In this review, we present a general perspective of the current state of knowledge of biofilm formation in B. subtilis. In particular, a special emphasis is placed on summarizing the most recent discoveries in the field and integrating them into the general view of these truly sophisticated microbial communities.